Monitoring deformation of seasonally frozen Yellow River bank soil: A synergetic application of the SBAS InSAR approach - Yuxin Mao; Honglan Ji; Zhen Yang (PLoS ONE, 2025)
The riverbanks of the Inner Mongolia reach of the Yellow River face persistent risks of deformation and collapse due to freeze-thaw cycles and hydrodynamic forces. However, most existing studies have concentrated on urban land subsidence or the stability of hydraulic structures, while long-term and multi-reach systematic monitoring of this seasonally frozen and meandering section remains scarce. Based on Sentinel-1A satellite data, this study employs the Small Baseline Subset InSAR (SBAS-InSAR) technique to derive the spatiotemporal characteristics of riverbank deformation, integrates channel migration information to examine the spatial relationship between channel evolution and bank deformation, and conducts long-term deformation pattern analyses in representative reaches. The results indicate that the riverbanks in this section are generally stable, with 96.5% of monitoring points showing an average annual deformation rate within ±30 mm/a. Nevertheless, significant deformation was detected in some areas between the Bayangaole and Toudaoguai hydrological stations, dominated by uplift and strongly influenced by river water level fluctuations. Subsidence primarily occurred along the outer banks of meander bends, where loose bank structures pose potential stability risks. Specifically, in the Shisifenzi area, the average annual deformation rate ranged from −20.1 to 24.8 mm/a, with subsidence concentrated at meander crests and cultivated land, potentially affecting levee stability and farmland safety. In the Wenbuhao area, rates ranged from −18.7 to 19.5 mm/a, with subsidence concentrated along the eastern riverbank, indicating localized erosion risks, while uplift mainly occurred in farmland farther from the river. This study reveals the differentiated response characteristics of various reaches under hydrodynamic forces and demonstrates that SBAS-InSAR is effective for monitoring riverbank deformation in complex environments. The findings provide reliable technical support for riverbank hazard prevention and the protection of riverfront infrastructure in seasonally frozen regions.